Early rhythm-control therapy for atrial fibrillation in patients with a history of stroke: a subgroup analysis of the EAST-AFNET 4 trial. Issue 1 (January 2023) - Jensen, Märit; Suling, Anna; Metzner, Andreas; Schnabel, Renate B; Borof, Katrin; Goette, Andreas; Haeusler, Karl Georg; Zapf, Antonia; Wegscheider, Karl; Fabritz, Larissa; Diener, Hans-Christoph; Thomalla, Götz; et al.
Summary: Background: Patients with atrial fibrillation and a history of stroke are at high risk of recurrent stroke and cardiovascular complications. In the EAST-AFNET 4 trial we showed that a systematic strategy of early rhythm control was associated with a lower risk of cardiovascular outcomes than usual care in patients with atrial fibrillation diagnosed in the past 12 months. In this pre-specified subgroup analysis we aimed to assess whether a strategy of early rhythm control is safe and can prevent adverse cardiovascular outcomes compared with usual care in such patients. Methods: EAST-AFNET 4 was a randomised, open-label trial with blinded-outcome assessment done at 135 hospitals and secondary care practices in 11 European countries. Adults with early atrial fibrillation (ie, diagnosed ≤12 months before enrolment) were randomly assigned (1:1) to either early rhythm control or usual care, with stratification according to site and variable block lengths used for concealment. The first primary outcome was time to first occurrence of the composite of cardiovascular death, ischaemic or haemorrhagic stroke, or hospital admission with worsening of heart failure or acute coronary syndrome. The second primary outcome was the number of nights spent in hospital in 1 year. The primary safety outcome was the composite of any death, stroke, or serious adverse events related to rhythm-control therapy. Here we present the results of these outcomes in patients with a history of stroke. Analyses were done in the intention-to-treat population. EAST-AFNET 4 is registered with ClinicalTrials.gov (NCT01288352 ), EudraCT (2010–021258–20), and ISRCTN (ISRCTN04708680). Findings: Between July 28, 2011, and Dec 30, 2016, 2789 patients were randomly assigned in the EAST-AFNET 4 trial to either early rhythm control (n=1395) or usual care (n=1394). Of these patients, five had no information on history of stroke and were excluded from this subgroup analysis. 217 (8%) patients had a history of stroke, of whom 110 were assigned to early rhythm control and 107 to usual care. The median age of participants with a history of stroke was 72·0 years (IQR 66·0–76·0). 95 (44%) participants were female and 122 (56%) were male. During a median follow-up of 4·7 years (3·5–6·4) for patients with a history of stroke, a first primary outcome event occurred in 18 (16%) of 110 patients in the early rhythm-control group (3·7 per 100 person-years) and 33 (31%) of 107 in the usual care group (7·4 per 100 person-years; hazard ratio [HR] 0·52, 95% CI 0·29–0·93). The mean number of nights spent in hospital per year was 5·1 (SD 13·2) for patients with a history of stroke assigned to early rhythm control and 6·6 (10·1) for those assigned to usual care (incidence rate ratio 0·87, 95% CI 0·55–1·38). Among patients with a history of stroke, primary safety events occurred in 17 (15%) patients in the early rhythm-control group versus 30 (28%) in the usual care group. Interpretation: In this prespecified subgroup analysis in patients with recently diagnosed atrial fibrillation and a history of stroke, the effects of early rhythm control were consistent with the findings of the primary analysis. As the evidence from this subgroup analysis is considered supportive and exploratory, further research is needed to confirm the safety and efficacy of this approach in patients with a history of stroke. Funding: German Ministry of Education and Research, German Center for Cardiovascular Research (DZHK), Atrial Fibrillation Network (AFNET), European Heart Rhythm Association, St Jude Medical-Abbott, Sanofi, and the German Heart Foundation.